Competition for inorganic carbon between oxygenic and anoxygenic phototrophs in a hypersaline microbial mat, Guerrero Negro, Mexico. (24th January 2013) - Finke, Niko; Hoehler, Tori M.; Polerecky, Lubos; Buehring, Benjamin; Thamdrup, Bo
Summary While most oxygenic phototrophs harvest light only in the visible range (400–700 nm, VIS), anoxygenic phototrophs can harvest near infrared light (> 700 nm, NIR). To study interactions between the photosynthetic guilds we used microsensors to measure oxygen and gross oxygenic photosynthesis (gOP) in a hypersaline microbial mat under full (VIS + NIR) and VIS illumination. Under normal dissolved inorganic carbon (DIC) concentrations (2 mM), volumetric rates of gOP were reduced up to 65% and areal rates by 16–31% at full compared with VIS illumination. This effect was enhanced (reduction up to 100% in volumetric, 50% in areal rates of gOP) when DIC was lowered to 1 mM, but diminished at 10 mM DIC or lowered pH. In conclusion, under full‐light illumination anoxygenic phototrophs are able to reduce the activity of oxygenic phototrophs by efficiently competing for inorganic carbon within the highly oxygenated layer. Anoxygenic photosynthesis, calculated from the difference in gOP under full and VIS illumination, represented between 10% and 40% of the C‐fixation. The DIC depletion in the euphotic zone as well as the significant C‐fixation by anoxygenic phototrophs in the oxic layer influences the carbon isotopic composition of the mat, which needs to be taken into account when interpreting isotopic biosignals in geological records.